Hybrid Rhodamine Fluorophores in the Visible/NIR Region for Biological Imaging. (11th June 2019) - Wang, Liulin; Du, Wei; Hu, Zhangjun; Uvdal, Kajsa; Li, Lin; Huang, Wei
Abstract: Fluorophores and probes are invaluable for the visualization of the location and dynamics of gene expression, protein expression, and molecular interactions in complex living systems. Rhodamine dyes are often used as scaffolds in biological labeling and turn‐on fluorescence imaging. To date, their absorption and emission spectra have been expanded to cover the entire near‐infrared region (650–950 nm), which provides a more suitable optical window for monitoring biomolecular production, trafficking, and localization in real time. This review summarizes the development of rhodamine fluorophores since their discovery and provides strategies for modulating their absorption and emission spectra to generate specific bathochromic‐shifts. We also explain how larger Stokes shifts and dual‐emissions can be obtained from hybrid rhodamine dyes. These hybrid fluorophores can be classified into various categories based on structural features including the alkylation of amidogens, the substitution of the O atom of xanthene, and hybridization with other fluorophores. Abstract : Rhodamin‐Fluorophore werden häufig als Molekülgerüste für die biologische Markierung und die Fluoreszenzbildgebung verwendet. Ihre Absorptions‐ und Emissionsspektren wurden mittlerweile auf den gesamten Nahinfrarotbereich (650–950 nm) ausgedehnt, sodass ein geeignetes optisches Fenster zur Verfolgung der Produktion, Bewegung und Lokalisation von Biomolekülen in Echtzeit zur Verfügung steht.